Design of Amperometric Biosensors for the Detection of Glucose Prepared by Immobilization of Glucose Oxidase on Conducting (Poly)Thiophene Films. (1st March 2018) - Pilo, Maria; Farre, Roberta; Lachowicz, Joanna Izabela; Masolo, Elisabetta; Panzanelli, Angelo; Sanna, Gavino; Senes, Nina; Sobral, Ana; Spano, Nadia
Abstract : Enzyme-based sensors have emerged as important analytical tools with application in diverse fields, and biosensors for the detection of glucose using the enzyme glucose oxidase have been widely investigated. In this work, the preparation of biosensors by electrochemical polymerization of (poly)thiophenes, namely 2, 2′-bithiophene (2, 2′-BT) and 4, 4′-bis(2-methyl-3-butyn-2-ol)-2, 2′-bithiophene (4, 4′-bBT), followed by immobilization of glucose oxidase on the films, is described. N-cyclohexyl-N′-(2-morpholinoethyl)carbodiimide metho- p -toluenesulfonate (CMC) was used as a condensing agent, and p -benzoquinone (BQ) was used as a redox mediator in solution. The glucose oxidase electrodes with films of 2, 2′-BT and 4, 4′-bBT were then tested for their ability in detecting glucose from synthetic and real samples (pear, apricot, and peach fruit juices).